The pharmacokinetic and pharmacodynamic properties and short-term outcome of a novel once-weekly PEGylated recombinant human growth hormone for children with growth hormone deficiency - Liang, Yan; Zhang, Cai; Wei, Haiyan; Du, Hongwei; Zhang, Gaixiu; Yang, Yu; Zhang, Hua; Gong, Haihong; Li, Pin; Song, Fuying; Xu, Zhuangjian; He, Ruoyi; et al. (Frontiers in Endocrinology, 2022)
Objectives: To investigate the pharmacokinetics (PK) and pharmacodynamics (PD) of Y-shape branched PEGylated recombinant human growth hormone (YPEG-rhGH) and evaluate its short-term efficacy and safety in children with growth hormone deficiency (GHD). Methods: A total of 43 children with GHD from 12 sites in China were enrolled in this randomized, multicenter, active-controlled, double-blind (YPEG-rhGH doses) trial. Patients were randomized 1:1:1:1 to 100, 120, and 140 μg/kg/week of YPEG-rhGH groups and daily rhGH 35 μg/kg/day groups. The treatment lasted 12 weeks. The primary outcome was the area under the curve of the change of insulin-like growth factor-1 (IGF-1). The secondary outcome was the height velocity (HV) increment at week 12. Results: A dose-dependent response of maximum plasma concentration (Cmax) and area under the concentration-time curves from 0 to 168 hours (AUC0-168h) were observed for YPEG-rhGH. The ratio of Cmax and the ratio of AUC0-168h from the first to the last dosing were 1.09~1.11 and 1.22~1.26 respectively. A YPEG-rhGH dose-dependent increase in area under effect curve (AUEC) of IGF-1 fold change was observed. Model-derived mean IGF-1 SDS was in the normal range for all three YPEG-rhGH doses. At week 12, HV was 7.07, 10.39, 12.27 cm/year, and 11.58 cm/year for YPEG-rhGH 100, 120, and 140 μg/kg/week and daily rhGH respectively. Adherence and safety were consistent with the profile of daily rhGH. No related serious adverse events were reported. Conclusion: The PK/PD suggests that YPEG-rhGH is suitable for the once-weekly treatment of pediatric GHD. YPEG-rhGH 120 ~ 140 μg/kg/week provides the closest HV increment with similar safety and tolerability compared to daily rhGH 35 μg/kg/day in children with GHD.